Multi-agent System for Documents Retrieval and Evaluation Using Fuzzy Inference Systems - Galina Ivanova; Ark Andreev; Marwa A. Shouman (Institute of Advanced Engineering and Science, 2016)
Recently the World Wide Web are packed with huge quantities of information. From this view the user finds it difficult to get the relevant informations due to the increased of their quantities. This paper uses multi-agent system uses intelligent agent in order to retrieval documents from the World Wide Web. The user by this system can easily get the relevant documents which to need them.Multi-agent System is combined with fuzzy inference system for ranking documents. The documents ranking score by cosine similarity using fuzzy inference system development and implemented much simpler than the traditional method which require mathematical equations.